Paciente femenino de 65 años presenta pterigion 4 grado con disminución de la agudeza visual ojo izquierdo. - Robles Rodríguez, Marisol Cecilia (2021)
ANTECEDENT: This research focuses on making known, the frequency of this ophthalmologo gical pathology such as Ocular Pterigium, its involutional fibrovascular, Triangular, Horizontal, appearance in the bulbar conjuntiva on the Unipolar and Bipolar cornea (affecting the temporal, Nasal part), the latter being frequent Unilateral or Bilateral. Aim: Evidence of risk factors for Pterigeon, being its involutive appearance in the bulbar conjuntiva, its highest rate of appearance conjuntiva, its highest rate of appearance is between 35 years to 60 years. Methodology: The descriptive, non experimental field and cross-sectional study, with a qualitative- quantitative approach refers to this clinical case a 60 – years- old female patient with IV pterygium, its application is of scientific observation technique, unstructured interview. Result: Within the studies of the pterygium, the treatment is surgical many after surgery by scraping and autoinsert, patients are left with the injured cornea, forming irregulard astigmatins when the pterygium invade the visual Axis causing visual loss, due to multiples surgeries for recurrence, cases of Diplopia due to simblepharon have also been observed. Conclusion: The determining factor of pterigeon is give by not altending on time With the health professional, one of its symptoms is aesthetic, since it is an involutional tissue, where the cornea, the glass of the eye, loses its circular appearance, observing a whitish tissue, more or less reddened, stains the image of the iris, the color of the eye, which is observed though the transparent cornea.